2017
DOI: 10.1007/s12192-017-0778-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the PDE5 inhibitor tadalafil on redox status and antioxidant defense system in C2C12 skeletal muscle cells

Abstract: Phosphodiesterase type 5 inhibitors (PDE5Is), widely known for their beneficial effects onto male erectile dysfunction, seem to exert favorable effects onto metabolism as well. Tadalafil exposure increases oxidative metabolism of C2C12 skeletal muscle cells. A rise in fatty acid (FA) metabolism, requiring more oxygen, could induce a larger reactive oxygen species (ROS) release as a byproduct thus leading to a redox imbalance. The aim of this study was to determine how PDE5I tadalafil influences redox status in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Clinical evidence sustains a strong association between PDE5i use and reduced mortality rate and hospitalization in a cohort of T2D patients with attendant high cardiovascular risk [ 28 ]. PDE5 inhibition seems also to exert favorable effects by enhancing enzymatic antioxidant system capacity [ 29 ]. Of note, those effects were not achieved with other class of vasoactive drugs as prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence sustains a strong association between PDE5i use and reduced mortality rate and hospitalization in a cohort of T2D patients with attendant high cardiovascular risk [ 28 ]. PDE5 inhibition seems also to exert favorable effects by enhancing enzymatic antioxidant system capacity [ 29 ]. Of note, those effects were not achieved with other class of vasoactive drugs as prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of C2C12 myotubes with tadalafil influences the metabolism by improving FAs oxidation, as displayed by the increase of 3-OH acylCoA dehydrogenase and citrate synthase activities, respectively, which are involved in β-oxidation and the Krebs cycle (Sabatini et al, 2011). Recently, we have reported that such increase in oxidative metabolism may be beneficial to skeletal muscle cells by enhancing the enzymatic antioxidant system capacity (Duranti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we have demonstrated that tadalafil improved oxidative capacity in C2C12 skeletal muscle cells in vitro, as displayed by an increased reliance on fat metabolism (Sabatini et al, 2011) accompanied by a better redox status (Duranti et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…TBARS levels were assayed by spectrophotometric analysis, as previously described [ 34 ]. The methodology calculates malondialdehyde (MDA) and other aldehydes generated by lipid peroxidation induced by hydroxyl free radicals.…”
Section: Methodsmentioning
confidence: 99%